The Legal Basis for The Emergence of Civil Liability of The Beneficial Owner in Agreements That Harm Third Parties - Khairul Hidayat; Elisatris Gultom; Tri Handayani (Green Publisher Indonesia, 2026)
This research examines the civil liability of beneficial owners in contractual relationships when third parties suffer losses. The issue arises because beneficial owners may substantially control corporate decisions and receive economic benefits without being formally recorded as shareholders, directors, or commissioners. This research uses a normative juridical method with a descriptive-analytical specification, supported by literature study and interviews with legal experts. The findings show that civil liability may be imposed based on the form of control exercised by the beneficial owner. If the beneficial owner is also a controlling shareholder, liability may be imposed through the doctrine of piercing the corporate veil under Article 3 paragraph (2) of Law Number 40 of 2007 concerning Limited Liability Companies. Meanwhile, hidden beneficial owners may be held liable under Article 1365 of the Indonesian Civil Code if factual control, bad faith, unlawful conduct, and a causal relationship with third-party losses can be proven. This study concludes that civil liability for beneficial owners is necessary to prevent misuse of corporate legal personality and strengthen legal protection for harmed third parties.